A highly selective naked-eye and fluorescent probe for fluoride ion based on 1, 8-naphalimide and benzothizazole. (June 2017) - Chen, Xiaoxing; Leng, Taohua; Wang, Chengyun; Shen, Yongjia; Zhu, Weihong
Abstract: Based on benzothizazole and 1, 8-naphalimide, a novel colorimetric and fluorescent probe (probe1 ) for fluoride ion was synthesized by Schiff base reaction. The striking yellow-to-blue color change of the probe1 in the CH3 CN was observed with the naked eyes only in presence of F − among the eight anions (F −, Cl −, Br −, I −, NO3 −, HSO4 −, H2 PO4 −, AcO − ). Besides that, upon addition of F −, both of the absorption and emission peaks shifted to near-infrared region (NIR) (>600 nm) in UV–vis and fluorescent spectra, and the detection limit reached as low as 0.41 μM. Furthermore, the 1 H NMR titration and theoretical calculation based on TD-DFT indicated that the fluoride ion induced deprotonation of the probe1 through hydrogen bonding interaction between amino group of probe1 and fluoride ion. Graphical abstract: A novel near-infrared fluorescent probe with high sensitivity and selectivity for fluoride ion has been fabricated. Highlights: The obvious color and fluorescence changes can be observed with naked eyes. Probe1 possesses good selectivity, low detection limit and fast response for F − . Probe1 displays ratiometric optical response to F − in near-infrared (NIR) region.